Digital measurement of radiographic tibial plateau angle. A comparison to measurement on printed digital images - Lister, S. A.; Roush, J. K.; Renberg, W. C. (Veterinary and Comparative Orthopaedics and Traumatology, 2008)
Pre-operative digital radiographs from 50 dogs undergoing a tibial plateau leveling osteotomy were evaluated. Tibial plateau angles were measured directly on printed films and measured on digital images using two different commercial DICOM viewers. The radiographs were scored for osteoarthritis and positioning. Using pooled results, the mean TPA from the digital images employing Web1000 (26.47° ± 3.90) was significantly higher then the mean TPA using film radiographs (25.41° ± 3.51), or IQ-View Pro (25.48° ± 3.89). There was not a significant difference between mean TPA using radiographs or IQ-view. Digital TPA measurement using built-in angle calipers in the clinical setting is a valid technique compared to measurements from film radiographs, and produces reproducible results. However, before changing to digital measurements, the chosen software programme should be validated against measurements using film radiographs to determine the magnitude of differences.
Keywords: TPA; TPLO; digital measurement; canine